Degradation of Tropical Malaysian Peatlands Decreases Levels of Phenolics in Soil and in Leaves of Macaranga pruinosa - Yule, Catherine M.; Lim, Yau Yan; Lim, Tse Yuen (Frontiers in Earth Science, 2016)
Indo-Malaysian tropical peat swamp forests (PSF) sequester enormous stores of carbon in the form of phenolic compounds, particularly lignin as well as tannins. These phenolic compounds are crucial for ecosystem functioning in PSF through their inter-related roles in peat formation and plant defenses. Disturbance of PSF causes destruction of the peat substrate, but the specific impact of disturbance on phenolic compounds in peat and its associated vegetation has not previously been examined. A scale was developed to score peatland degradation based on the three major human impacts that affect tropical PSF – logging, drainage and fire. The objectives of this study were to compare the amount of phenolic compounds in Macaranga pruinosa, a common PSF tree, and in the peat substrate along a gradient of peatland degradation from pristine peat swamp forest to cleared, drained and burnt peatlands. We examined phenolic compounds in M. pruinosa and in peat and found that levels of total phenolic compounds and total tannins decrease in the leaves of M.pruinosa and also in the surface peat layers with an increase in peatland degradation. We conclude that waterlogged conditions preserve the concentration of phenolic compounds in peat, and that even PSF that has been previously logged but which has recovered a full canopy cover will have high levels of total phenolic content (TPC) in peat. High levels of TPC in peat and in the flora are vital for the inhibition of decomposition of organic matter and this is crucial for the accretion of peat and the sequestration of carbon. Thus regional PSF flourish despite the phenolic rich, toxic, waterlogged, nutrient poor, conditions, and reversal of such conditions is a sign of degradation.